Phytochemical Composition of Extractives in the Inner Cork Layer of Cork Oaks with Low and Moderate Coraebus undatus Attack - Simões, Rita (2022)
The beetle Coraebus undatus, during its larval stage feeds, and excavates galleries on the cork-generating layer of Quercus suber L. trees, seriously affecting the cork quality with significant economic losses for the cork industry. This work compared the composition of the extracts present in the innermost cork layers (the belly) of cork planks from Q. suber trees with low and moderate C. undatus attack in one stand. The total extractives in the inner cork layer from trees with moderate and low C. undatus attacks were similar (on average 22% of the cork mass) with a high proportion of polar compounds (91% of the total extractives). The chemical composition of the inner cork lipophilic extractives was the same in trees infested and free of larvae, with triterpenes as the most abundant family accounting for 77% of all the compounds, predominantly friedeline. The hydrophilic extractives differed on the levels of phenolic compounds, with higher levels in the inner cork extracts of samples from trees with low attack (90.0 mg GAE g1 vs. 59.0 mg GAE g1 of inner cork mass) The potential toxic activity of phenolic compounds may have a role in decreasing the larval feeding